The use of external representation in academic oral presentations among international undergraduate students in higher education - Mikal, Erlinda (Universiti Malaysia Sarawak (UNIMAS), 2015)
In previous studies, one of the chaIllenges that international students faced was conducting academic oral presentations. The problems encountered by the students were related to linguistics, content, and presentation skills. In terms of presentation skills, the international students claimed that they lacked the skills to organize their ideas and present them using Power Point slides. Most studies in this field were done on improving language and little was done on skills to organize their ideas to be externally presented using PowerPoint slides. External representation was claimed to assist learners to organize thoughts. Therefore, this study looks at the use of external representation in organizing students' thoughts and speaking fluency in academic oral presentation among international undergraduate students in UNIMAS. The research was done qualitatively in which 12 international undergraduate students were interviewed and assessed. The interview questions focused on the challenges the students face in academic oral presentations, their experience in using any form of external representation, their perceptions on the use of external representation and its effect on their speaking fluency. Then, the informants were assessed based on their fluency using presentation rubric. The results had shown that the students had varied perceptions on the use of external representation and the effects on their English speaking fluency.